Determinants that influence green product purchase intention and behavior: a literature review and guiding framework - Wijekoon, Rusitha; Sabri, Mohamad Fazli (Multidisciplinary Digital Publishing Institute, 2021)
Environmental deterioration brought about by consumers’ non-feasible utilization pattern is putting a pressure on the environment and is obstructing sustainable development. To hinder this impact and stimulate a more sustainable economic growth, one solution is to lessen or move utilization patterns from conventional products to eco-friendly products. The authors conducted a review study of green purchase behavioral research across the 6-year period from 2015 to 2021, identifying 108 studies that met our inclusion criteria. The current review distinguishes different pervasive facilitators, motives, and obstacles influencing consumers’ decision-making process towards environmentally friendly products, and it gives potential clarifications for contradictions found in green purchase behavior (GPB). The paper reveals the main determinants of consumer’s GPB, and as a result of the review, 212 variables that affect green purchase intention (GPI) were identified. Moreover, 135 determinants that influence GPB were recorded. In this way, besides contributing to the literature, it will assist policymakers in formulating and employing strategies to persuade eco-friendly purchasing, and it will give an opportunity for marketers to generate proper marketing strategies for drawing in clients and guaranteeing ideal sales.